Comparison of the Effect of Linear and Nonlinear Methods on Children's Actual - Amin Ebdalifar; Shahab Parvinpour; Sayed Mohammadkazem Vaez Mousavi (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims Education in school is a key element of health and helps to freshness and vitality of the community through the promotion of the physical activity. In this regard, some practitioners try to be effective in community health through linear or non-linear training methods. Thus, this study tried to determine which educational method (linear, nonlinear) is effective in promoting perceived and real motor competence in children.Methods In this study, two boy schools were selected whose education in the physical education class was linear in one and non-linear in the other. Therefore, 50 children from each school were selected as a sample randomly (Mean±SD age: 8.47±1.14 ). Motor proficiency was assessed by the Bruininks-Oseretsky Test, and perceived motor competence was assessed by the Incentive Motivation Questionnaire. Results The results of the analysis of covariance by eliminating the effect of the pre-test showed that the nonlinear group in motor skills (P=0.00) and perceived motor competence (P=0.02) scored significantly higher than the linear groupConclusion The results emphasize the importance of using nonlinear training in physical education with manipulation of the environment and task without direct instructions and feedback. Nonlinear methods as new methods in schools can replace traditional methods. In this method, by manipulating the constraints, children can be helped to grow in various dimensions, including real and perceived motor skills. The results of this study are useful for teachers who teach basic motor skills in school.